2022
DOI: 10.1136/bmjopen-2021-058266
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and physical experiences of people with neovascular age-related macular degeneration during the injection process in Germany: a qualitative study

Abstract: ObjectivesIn order to better understand the continued barriers to the provision of vascular endothelial inhibitor therapy, this study aims to investigate patients’ experiences with neovascular age-related macular degeneration (nvAMD) in Germany during the injection process and how they deal with it.Design and participantsThis analysis is part of the qualitative arm of a wider mixed-methods study. We recruited participants all over Germany via ophthalmologists, eye clinics, general practitioners, care bases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Our study revealed a highly adherent patient group who did not consider opting out of treatment because they find the course of treatment somehow unproblematic and without significant barriers. In contrast, a recent study by Thier et al 17 with nAMD patients in Germany found that the pain associated with therapy and a lack of perceived positive effects led individuals with significant vision loss to discontinue treatment. Effective communication strategies were identified as crucial in preventing patients from discontinuing therapy, a recommendation echoed in the work of Hüsler and Schmid 18 from Switzerland.…”
Section: Discussionmentioning
confidence: 86%
“…Our study revealed a highly adherent patient group who did not consider opting out of treatment because they find the course of treatment somehow unproblematic and without significant barriers. In contrast, a recent study by Thier et al 17 with nAMD patients in Germany found that the pain associated with therapy and a lack of perceived positive effects led individuals with significant vision loss to discontinue treatment. Effective communication strategies were identified as crucial in preventing patients from discontinuing therapy, a recommendation echoed in the work of Hüsler and Schmid 18 from Switzerland.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, these three main factors (frequency, efficacy, side effects) are central to DCE studies carried out in the context of wet AMD injections ( 16 – 18 ). Some additional factors, such as waiting time in clinic and the pain or discomfort associated with injections, are also known to be burdensome for patients undergoing regular intravitreal treatment for wet AMD ( 19 ). We included waiting time in the scenario options because this was an important concern for the patient advisors; however, this was held constant across options, on the basis that the actual injection procedure and time in clinic would be similar whatever the treatment regimen.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of patient–practitioner interaction has been highlighted in qualitative studies of the experience of patients with neovascular AMD5 23–26; however, there is a paucity of literature describing qualitative perspectives in the assessment of pain and anxiety related to anti-VEGF injections that incorporate a practitioner perspective. This study examined patients’ experiences of injections and combined them with the practitioners’ views from a qualitative perspective.…”
Section: Introductionmentioning
confidence: 99%